EVALUATION OF A TELEMEDICINE MODEL TO FOLLOW UP PATIENTS WITH EXUDATIVE AGE-RELATED MACULAR DEGENERATION. Issue 2 (February 2016) - Andonegui, Jose; Aliseda, Daniel; Serrano, Luis; Eguzkiza, Aitor; Arruti, Natalia; Arias, Luis; Alcaine, Araceli
Abstract : Purpose: To evaluate a telemedicine model to follow up patients with exudative age-related macular degeneration and compare the time spent using this model with the time spent conducting office examinations. Methods: Results of office and telemedicine evaluations were compared to determine whether patients with exudative age-related macular degeneration previously treated with intravitreal injections needed additional treatment. The office examinations included visual acuity measurement, fundus examination, and optical coherence tomography. The telemedicine evaluation included evaluation of retinography images, optical coherence tomography images, and visual acuity data obtained in the office. We also measured the time spent on telemedicine evaluations and compared it with the time spent on office examinations. Results: Twenty-one patients were included. A comparison of office and remote diagnostic decisions showed the same results in 181 cases. Among the 20 remaining patients and considering office diagnostic decisions as the gold standard, 17 (8%) patients had false-positive diagnoses and 3 (1%) had false-negative diagnoses. The sensitivity and specificity of the telemedicine evaluations were 96% and 85%, respectively. The average time spent on remote evaluations was 1 minute 21 seconds compared with 10 minutes spent on office examination ( P < 0.001). Conclusion: The telemedicine model can be a useful alternative for following up patients with age-related macular degeneration. Abstract : The objective of this study was to evaluate a telemedicine model to follow up patients with exudative age-related macular degeneration and compare the time spent using this model with the time spent conducting office examinations. The results indicated that telemedicine can be a useful alternative for following up patients with exudative age-related macular degeneration.